The myth about the origin of the Karo House - Ginting, Juara R. (UI Scholars Hub, 2010)
The Karo people in North Sumatra (Indonesia) consider areas in the Karo regency and those in other regencies as part of Taneh Karo (the Karolands), despite the fact that these areas comprise different administrative territories. This paper focuses on how the idea of Taneh Karo is articulated in a special Karo myth. Scholarly research has discovered that the notion of Taneh Karo originated in pre-colonial times, but an analysis of a local myth which established the concept of Taneh Karo remains an interesting anthropological study. This study is significant as it endeavours to comprehend the traditional ways of life of the Karo people, and it is a crucial attempt to map out the inter-group relations in the Karo area, where the Acehnese, the Batak, and the Malay people take part. It is interesting to note that the myth of Karo has positioned the Karo community and land in a distinctive site within the network of inter-related groups. This is precisely the position which would determine the formation of the Karolands.